Physics-aware macromodels for MEMS switches - Lup, Aurel-Sorin; Ciuprina, Gabriela; Ioan, Daniel; Duca, Anton; Nicoloiu, Alexandra; Vasilache, Dan (Compel, 2020)
Purpose The purpose of this paper is to propose a physics-aware algorithm to obtain radio frequency (RF)-reduced models of micro-electromechanical systems (MEMS) switches and show how, together with multiphysics macromodels, they can be realized as circuits that include both lumped and distributed parameters. Design/methodology/approach The macromodels are extracted with a robust procedure from the solution of Maxwell’s equations with electromagnetic circuit element (ECE) boundary conditions. The reduced model is extracted from the simulations of three electromagnetic field problems, in full-wave regime, that correspond to three configurations: signal lines alone, switch in the up and down positions. Findings The technique is exemplified for shunt switches, but it can be extended for lateral switches. Moreover, the algorithm is able take frequency dependence into account both for the signal lines and for the switch model. For the later, the order of the model is increased until a specified accuracy is achieved. Originality/value The use of ECE as boundary conditions for the RF simulation of MEMS switches has the advantage that the definition of ports is unambiguous and robust as the ports are clearly defined. The extraction approach has the advantage that the simplified model keeps the basic phenomena, i.e. the propagation of the signal along the lines. As the macromodel is realized with a netlist that uses transmission lines models, the lines’ extension is natural. The frequency dependence can be included in the model, if needed.